Analysis of correlation between cerebrospinal fluid and plasma HIV-1 RNA levels in patients with neurological opportunistic diseases - Christo, Paulo Pereira; Greco, Dirceu Bartolomeu; Aleixo, Agdemir Waleria; Livramento, Jose António (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
The question of whether HIV-1 RNA in cerebrospinal fluid (CSF) is derived from viral replication in the central nervous system or simply reflects the transit of infected lymphocytes from the blood compartment has long been a matter of debate. Some studies found no correlation between CSF and plasma viral load, whereas others did. The lack of a correlation between the two compartments suggests that the presence of HIV-1 RNA is not simply due to the passive passage of the virus from blood to CSF but rather due to intrathecal replication. To evaluate the correlation between plasma and CSF HIV-1 RNA levels and to identify situations in which there is no correlation between the two compartments, seventy patients were prospectively studied. The association between CSF and plasma viral load was evaluated in the total population and in subgroups of patients with similar characteristics. A correlation between the CSF and plasma compartments was observed for patients undergoing highly active antiretroviral therapy (HAART), those with a CD4 T lymphocyte count lower than 200 cells/mm³, and those with increased CSF protein content. On the other hand, no correlation was observed for patients without adequate virological control, who had a CD4 count higher than 200 cells/mm³ and who did not use HAART. The correlation between the two compartments observed in some patients suggests that CSF HIV-1 RNA levels may reflect plasma levels in these subjects. In contrast, the lack of a correlation between the two compartments in patients who were not on HAART and who had normal CSF proteins and a poor virological control possibly indicates compartmentalization of the virus in CSF and, consequently, plasma-independent intrathecal viral replication. Tem sido objeto de debate a questão se o RNA do HIV-1 no líquido cefalorraquidiano (LCR) é derivado da replicação viral no sistema nervoso central ou simplesmente reflete o tráfego de linfócitos infectados do compartimento sanguíneo. Alguns estudos não mostraram correlação entre a carga viral do plasma e LCR, mas outros sim. A falta de correlação entre os dois compartimentos sugere que a presença de RNA do HIV-1 não é simplesmente devido à passagem do vírus do plasma para o LCR, mas sim a uma replicação intratecal. Para avaliar a correlação entre os níveis de RNA do HIV-1 no plasma e no LCR e tentar identificar situações, na qual, não existe a correlação entre os dois compartimentos avaliaram-se setenta pacientes prospectivamente. A associação entre a carga viral do LCR e plasma foi avaliada na população total e em subgrupos de pacientes com características similares. A correlação entre os dois compartimentos foi observada em pacientes que estavam em uso da terapia antiretroviral (HAART), naqueles que tinham contagem de linfócitos CD4 menor que 200 céls/mm³ e naqueles com aumento da concentração de proteínas no LCR. Por outro lado, não houve correlação para os pacientes que não tinham um controle virológico adequado, os que tinham contagem de CD4 maior que 200 céls/mm³ e aqueles que não estavam usando HAART. A correlação entre os dois compartimentos observada em alguns pacientes sugere que os níveis de RNA do HIV-1 no LCR podem refletir os níveis plasmáticos nestes pacientes. E a falta de correlação ente os dois compartimentos em pacientes que não usavam HAART, nos que tinham uma concentração de proteínas no LCR normal, e nos que não apresentavam bom controle virológico, indica provavelmente a compartimentalização do vírus no LCR e consequentemente replicação viral intratecal independente da do plasma.